High Levels of Proinflammatory Cytokines, but Not Markers of Tissue Injury, in Unaffected Intestinal Areas from Patients with IBD - Alberto J. León; Emma Gómez; Jose A. Garrote; David Bernardo; Asterio Barrera; Jose L. Marcos; Luis Fernández-Salazar; Benito Velayos; Alfredo Blanco-Quirós; Eduardo Arranz (Mediators of Inflammation)
Intestinal alterations in IBD are triggered and maintained by an overexpression of proinflammatory cytokines. Additionally, increased immune activation has been found in the adjacent intestinal areas without displaying any apparent histological alterations, however, the regulatory environment is not well established. Biopsy specimens from patients with ulcerative colitis (UC) and Crohn's disease (CD), from both affected and unaffected areas, and also from a group of colonic biopsies from healthy controls, were included in our study. Cytokines and markers of mucosal damage were analyzed by real-time PCR, and some of the results confirmed by western-blot and ELISA. Levels of IFNγ, TNFα, IL-6, IL-15, IL-18, and IL-23 were increased (above healthy controls) in both affected and unaffected areas from IBD. IL-1β, IL-6, IL-12, and IL-27 were higher in affected areas compared to unaffected ones in UC but not CD. In general, a correlation was observed between mRNA levels of these cytokines and both iNOS and Granzyme B. SOCS-2 and SOCS-3 were also increased in the affected areas. In conclusion, the unaffected areas from IBD show increased levels of a restricted set of cytokines that may exert immune activating roles in these areas without being able to trigger tissue damage.